О Сергее Радлове и Осипе Мандельштаме (По архивным источникам) [Sergei Radlov and Osip Mandel’shtam: Some Newly Discovered Sources] - Marina Salman (Slavica Revalensia)
This article aims at summarizing the life story of a Russian theater director Sergei Radlov (1892—1958) with an emphasis on his friendship with Osip Mandel’shtam. It includes a whole series of previosly unpublished Radlov’s letters to various correspondents, confirsm Radlov’s co-authorship of the collective play Kofeinia razbitykh serdets (The Coffee Shop of Broken Hearts), and establishes a new event in Mandel’shtam’s life: his poetry recital with Nikolai Gumilev at the Radlovs.